Sanksi Hukum terhadap Pelaku Penyadapan Telepon Pintar atau Smartphone Melalui Aplikasi Android Modifikasi Ilegal yang Diinstal oleh Korban - I Made Arimbawa Wiraputra; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2022)
Technological advances have resulted in illegal wiretapping crimes being carried out more easily, namely by utilizing illegal modification applications. The purpose of this research is to analyze the legal protection of the personal data of smartphone tapping victims as a result of installing an illegal modified android application made by the perpetrator and to examine criminal sanctions against smartphone tapping perpetrators through an illegal modified android application made by the perpetrator. This research uses a normative legal research method, using a statutory approach and a conceptual approach. There are two types of sources of legal materials in this research, namely primary sources of legal materials and secondary sources of legal materials. Primary legal materials come from statutory regulations related to the issues studied, while secondary legal materials come from law books and legal journals that are related to this research. The data collection technique used library techniques, which carried out a literature research on legal materials, both primary legal materials and secondary legal materials. From the results of the research, Indonesia does not have a law that specifically and legally regulates the protection of personal data. There are two forms of legal protection for the personal data of victims of illegal wiretapping, namely, preventive and repressive legal protection. Regarding wiretapping, it is regulated in the Telecommunications Law and the ITE Law. Both laws expressly prohibit illegal wiretapping and for those who do illegal wiretapping who use illegal modification applications can be subject to sanctions in accordance with article 50 of the ITE Law. The government is advised to further research the draft law before ratifying it so that there is no conflict of norms.